MAPPING SPATIAL VARIATION IN SURFACE SOIL WATER CONTENT: COMPARISON OF GROUND-PENETRATING RADAR AND TIME DOMAIN REFLECTOMETRY - Huisman J.A.; Snepvangers J.J.J.C.; Bouten W.; Heuvelink G.B.M. (My University, 2002)
Mapping soil water content (SWC) is a difficult but important task in many fields, such as hydrology, agronomy and soil science. Ground-penetrating radar (GPR) is a valuable technique to measure surface SWC at an intermediate scale in between the scales of time domain reflectometry (TDR) and remotely sensed data. To measure SWC with GPR, the surface soil permittivity was determined with the ground wave velocity. The first aim of this study was to evaluate the potential of GPR to measure spatial SWC variation. The second aim was to compare GPR and TDR with respect to the type of spatial SWC structures that can be measured by these methods. A spatial structure in SWC was created by heterogeneous irrigation with sprinklers of various intensities. Then spatial SWC variation was measured with both GPR and TDR. The experiment showed that GPR is well able to measure spatial SWC variation as expressed by the variogram. The larger measurement volume of GPR filtered out small-scale spatial variation (<1.5m) and the large number of easily acquired GPR measurements resulted in well-defined and smooth experimental variograms. A comparison of interpolated SWC maps before and after irrigation showed that GPR is better suited than TDR for mapping large-scale features (>5m) in SWC. Especially the boundaries between areas with different SWC were better resolved in case of GPR because of the large number of GPR measurements obtained with the same measurement effort. Small-scale features (<5m) were not mapped adequately by either GPR or TDR. However, the chance of detecting small-scale features in SWC mapping at the field scale is higher for GPR, simply because of the higher sampling density.
Keywords: SOIL MOISTURE; GROUND-PENETRATING RADAR; TIME DOMAIN REFLECTOMETRY; SPATIAL VARIATION